A simplified 2D model to study the contact–friction at the interfaces of steel–concrete composite beam-to-beam joint. (1st February 2015) - Guezouli, Samy; Kaing, Sao Serey; Lachal, Alain
Highlights: Composite beam-to-beam joint. 2D Non-linear F.E. model. Influence of the butt-plate thickness. Investigation on the force transfer mechanism. Part of the resistance by friction. Abstract: This paper deals with a numerical investigation of the behavior of a new joint typology to connect continuously composite beams in bridges. This beam-to-beam joint consists of butt-plates and headed stud anchors connected to a transverse concrete beam. It has been designed and tested under fatigue and monotonic loading. To describe the joint behavior, a general 3D model is required. However, due to the nonlinearities involved (plasticity, cracking, contact, friction, etc.) the convergence of the iterative process is very difficult to reach with such a model. For an accurate interpretation of the test results and a better understanding of specific local behavior, not accessible to measurement, an equivalent 2D finite element model has been proposed to approach the actual 3D problem. After calibration against experimental data, performances of this 2D model have been illustrated through two studies: the parametric influence of the butt-plate thickness and the internal force transfer mechanism in the joint.